2015
DOI: 10.1155/2015/320701
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture in Children with Nocturnal Enuresis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background. Nocturnal enuresis (NE) is recognized as a widespread health problem in young children and adolescents. Clinical researches about acupuncture therapy for nocturnal enuresis are increasing, while systematic reviews assessing the efficacy of acupuncture therapy are still lacking. Objective. This study aims to assess the effectiveness of acupuncture therapy for nocturnal enuresis. Materials and Methods. A comprehensive literature search of 8 databases was performed up to June 2014; randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
(54 reference statements)
0
37
0
1
Order By: Relevance
“…In this study, randomized controlled trials which compared acupuncture therapy and pharmacological therapy or placebo treatment were identified, and a meta-analysis was performed. The results of meta-analysis of this study showed that acupuncture therapy is more effective for clinical efficacy when compared with placebo or pharmacological treatment, but this study suggested additional RCTs with rigorous experimental design, large-scale high quality methodological control, long follow-ups, and strict reporting specification [6]. Another systematic review was done about acupuncture for nocturnal enuresis in children.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In this study, randomized controlled trials which compared acupuncture therapy and pharmacological therapy or placebo treatment were identified, and a meta-analysis was performed. The results of meta-analysis of this study showed that acupuncture therapy is more effective for clinical efficacy when compared with placebo or pharmacological treatment, but this study suggested additional RCTs with rigorous experimental design, large-scale high quality methodological control, long follow-ups, and strict reporting specification [6]. Another systematic review was done about acupuncture for nocturnal enuresis in children.…”
Section: Discussionmentioning
confidence: 82%
“…Three mechanisms were imaged for NE including: bladder over-activity, failure to awaken in response to bladder sensations, and excessive nocturnal urine production [5]. The current acceptable treatments for NE are oral pharmacological therapies, including desmopressin, tricyclics, and oxybutynin, and behavioral therapies [6]. Desmopressin has been proven to have reliable effects on one third of the unselected enuretic children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Nocturnal enuresis affects 5% to 10% of the younger school-age children. [2] The frequency and severity of wetting episodes progressively increases with age, and children over 10 years of age have significantly more day time urinary symptoms and incontinence. [3] The enuresis appears as monosymptomatic, with no daytime urinary symptoms and nonmonosymptomatic which is accompanied by day time urinary symptoms.…”
Section: Introductionmentioning
confidence: 99%